Comparison of Dialogue Method with Android-Based Image Media and Dialogue Method Without Media to Vocabulary Mastery and Speaking Skills - Lili Fitriawati. S; Sitti Aida Azis; R. Rukli (Universitas Muhammadiyah Enrekang, 2022)
This study aims to determine whether there is a difference in the simultaneous mastery of vocabulary and speaking skills of students who follow the dialogue method with android-based image media and those who follow the dialogue method without media. The type of research used is Quasi Experimental Design with the type of Nonequivalent Control Group Design. The population of this research is all elementary schools in Buntu Batu DistrictThe research sample was 20 students of class III SDN 89 URU and 20 students of class III SDK TO'PAE, using cluster random sampling technique. Data collection techniques in this study were carried out using test techniques to determine vocabulary mastery in the form of multiple-choice questions and oral speaking skills tests. The results of the research based on descriptive analysis showed that the control class was 85,500 and the control class was 55,750. While the results of the inferential analysis indicated that the dialogue method with android-based image media had simultaneous differences in vocabulary mastery and speaking skills with a sig value of 0.00<0.05. The results of the Manova test. It means that the dialogue method with android-based image media is better than the dialogue method without the media.